2014
DOI: 10.1038/srep04250
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a living coral reef in the coastal waters of Iraq

Abstract: Until now, it has been well-established that coral complex in the Arabian/Persian Gulf only exist in the coastal regions of Bahrain, Iran, Kuwait, Oman, Qatar, Saudi Arabia, and United Arab Emirates and it was thought that there are no coral reefs in Iraq. However, here for the first time we show the existence of a living 28 km2 large coral reef in this country. These corals are adapted to one of the most extreme coral-bearing environments on earth: the seawater temperature in this area ranges between 14 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…in Cape Verde [ 64 ], Gulf of Guinea [ 65 ], and our model correctly predicts their presence, these reefs have not yet been charted and therefore do not appear in the observational data. Additionally, new reefs are constantly being discovered [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…in Cape Verde [ 64 ], Gulf of Guinea [ 65 ], and our model correctly predicts their presence, these reefs have not yet been charted and therefore do not appear in the observational data. Additionally, new reefs are constantly being discovered [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iraqi coral reefs are offshore, distributed within a space of approximately 28 km 2 , at depths ranging between 7-20 m (Pohl et al, 2014) (Map 1). The study area is located in the northwest Arabian Gulf between 29°36'30´´N -29°39'20.94´´N latitude and 48°48'21.2´´E -48°49'89.1´´E longitude (Map 2, Tab.…”
Section: Methodsmentioning
confidence: 99%
“…In the ocean, where aragonite saturation decreases, the effect will tend to favor organisms that create the more stable forms of calcium carbonate, such as calcite and high magnesium calcite; aragonite-creating organisms, like corals, will in turn be subject to more dissolution and bio-erosion, calcification of all groups, however; is negatively affected by the decrease in the carbonate saturation of sea waters (Feely et al, 2004). Coral reefs in the northern and northwestern territories of the Arabian Gulf are exposed to a very heavy load of particles that derive their input from the Shatt Al-Arab River of Iraq; nine species of coral reefs we are discovered in the Iraqi marine environment between September of 2012 and May of 2013 by Marine Science Center (MSC) of Basrah, Iraq and Scientific Diving Center (SDC) of Freiberg ,Germany (Pohl et al,2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, coral reefs worldwide are impacted by global climate change and anthropogenic disturbances [ 2 , 3 , 4 ]. Three chemical pollution categories have generally attracted attention in marine systems: oil and oil derivatives [ 2 , 5 ], heavy metals [ 6 , 7 ], and synthetic organics such as pesticides and herbicides [ 8 , 9 ]. The most important forms of anthropogenic disturbance to coral reefs include additional threats such as damages associated with fishing activities, euthrophication and pollution caused by sewage discharge, heat stress caused by effluents from power plants, and sedimentation from dredging and mud dumping (as reviewed by [ 10 , 11 , 12 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, industrial development has caused serious metal pollution, where metals accumulate in marine sediments [ 6 , 7 , 45 , 46 ] and marine organisms [ 47 , 48 ] in many coastal areas worldwide [ 12 , 14 , 49 ]. In Taiwan, investigators reported bio-accumulation of metals in plankton [ 50 , 51 ], as well as in sediments and benthic organisms [ 11 , 52 , 53 ], and scleractinian corals [ 54 ].…”
Section: Introductionmentioning
confidence: 99%